Analysis of the Effect of Employee Engagement, Perceived Organizational Support, and Motivation on Employee Performance Study at PT. Dino Jaya Karya - Khusniah Khusniah; Didik Subiyanto; Epsilandri Septyarini (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This research was conducted with the aim of knowing the effect of employee engagement, perceived organizational support, and motivation on the performance of employees of PT. Dino Jaya Karya. This research uses descriptive research with a quantitative approach. The data collection technique was carried out using a questionnaire media with the Likert method. The population in this study were 80 permanent employees of PT. Dino Jaya Karya. The sampling technique used is using a saturated sample (total sampling). The total sampling obtained is as many as 80 employees from PT. Dino Jaya Karya. The t test shows that the employee engagement variable (X1) has a positive and significant effect on the employee performance variable (Y) with a value of 0.000, the perceived organizational support variable (X2) has a positive and significant effect on employee performance ( Y) with a value of 0.000, and the motivation variable (X3 has a positive and significant effect on employee performance variable (y) with a value of 0.004. In the F test results employee engagement, perceived organizational support, and motivation have a simultaneous effect on employee performance as indicated by a significance value of 0.000. Keywords: Employee engagement, perceived organizational support, motivation, employee